Surface plasmon resonance imaging for affinity-based biosensors - Scarano, Simona; Mascini, Marco; Turner, Anthony P. F.; Minunni, Maria E. (Elsevier, 2010)
SPR imaging (SPRi) is at the forefront of optical label-free and real-time detection. It offers the possibility of monitoring hundreds of biological interactions simultaneously and from the binding profiles, allows the estimation of the kinetic parameters of the interactions between the immobilised probes and the ligands in solution. We review the current state of development of SPRi technology and its application including commercially available SPRi instruments. Attention is also given to surface chemistries for biochip functionalisation and suitable approaches to improve sensitivity.
Keywords: Surface plasmon resonance imaging; SPRi; Affinity sensing; Immobilisation chemistry; Signal amplification immunosensor; Aptasensor; Optical sensor